2019
DOI: 10.31557/apjcp.2019.20.8.2397
|View full text |Cite
|
Sign up to set email alerts
|

Risk Modulation of Oral Pre Cancer and Cancer with Polymorphisms in XPD and XPG Genes in North Indian Population

Abstract: Background:Environmental carcinogens cause DNA damages which if not repaired properly, may increase the risk of cancer. The Xerodermapigmentosum group D (XPD) and group G (XPG) genes are essential genes for DNA repair and alteration in DNA repair causes cancer. The present study aimed to evaluate the relationship between XPD and XPG polymorphisms and risk of oral pre cancer and cancer. Methods:Present study genotyped 302 samples of oral diseases and 300 controls for XPD (A/C) and XPG (G/C) polymorphisms with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…[ 25 ] and the meta-analysis by Flores-Obando RE et al . [ 26 ] and Zhang et al ,[ 27 ] and the case–control study by Avci, Iplik, Aydemir et al ,[ 28 ] and Nigam et al [ 20 ] All of these studies suggested that polymorphism in the XPD gene could play a role in the development of OSCC [ Table 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 25 ] and the meta-analysis by Flores-Obando RE et al . [ 26 ] and Zhang et al ,[ 27 ] and the case–control study by Avci, Iplik, Aydemir et al ,[ 28 ] and Nigam et al [ 20 ] All of these studies suggested that polymorphism in the XPD gene could play a role in the development of OSCC [ Table 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…About 98% of the normal healthy individuals show no polymorphism. The XPG gene harboured SNPs and many of the SNPs alter the risk of different cancers such as colorectal, lung, and laryngeal cancer as reported from the study done by Nigam et al [ 20 ] [ Table 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found a negative correlation between BMI levels and 8-OHdG levels in the body. Low body weight may increase the oxidative damage of DNA by smoking and other factors (Nigam et al, 2019;Tang et al, 2018a, b;Chang et al, 2016), thereby promoting tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that XPd gene polymorphism increases the risk of lung cancer in residents of coal mines (8). XPD polymorphisms are associated with the development of pre oral cancer as well as oral cancer and its clinical course (9). It has been found that XPd can inhibit the proliferation and migration of hepatocellular carcinoma cells (10).…”
Section: Introductionmentioning
confidence: 99%